PENERAPAN HUKUM PIDANA YANG MEMBERIKAN EFEK JERA BAGI PELAKU TINDAK PIDANA SEKSUALITAS - Dwi Putri (VIVA THEMIS, 2018)
Sexual crime is an inhumane crime so sanctioning the perpetrators is very important to provide a deterrent effect by upholding the true justice. then that became the subject matter in this writing on the provision of sanctions that provide a deterrent effect for the perpetrators of criminal acts of sexuality. Problem approach using normative juridical approach (legal research). For perpetrators Sexual violence must be given sanctions that create a deterrent effect so that no longer repeat its actions as regulated in the Child Protection Act No. 35 of 2014 on the Change of Child Protection Act No. 23 of 2002. And also the Criminal Code. Law enforcers must be firm in dealing with cases of sexual violence. Sexual violence perpetrators must be punished according to their actions, the perpetrator should also get rehabilitation of his sexual disorders.